Analisis Finansial Budidaya Keramba Ikan Nila Di Desa Keranggan Kabupaten Muaro Jambi (Studi Kasus Desa Keranggan) - Etik Winarni; Ali Fahmi; Yolanda Sari; Mustika Mustika; Alamsyah Alamsyah (Universitas Batanghari, 2022)
This study aims to determine the social and economic characteristics of fish cages and to analyze the financial feasibility of tilapia cage cultivation in Keranggan Village, Muaro Jambi Regency. Data collection in this study used observational data, namely filling out questionnaires and direct interviews with tilapia fish cage business actors in Keranggan Village, Muaro Jambi Regency. The location selection was carried out with the consideration that the businesses that became the object of this study were widely spread in Muaro Jambi Regency, especially in Keranggan Village, Sekernan District. The population in this study were tilapia cage farmers, namely the cultivators themselves (the owners of the cultivators). The fish cage business in Keranggan Village is 25 units of tilapia fish cage business, the data studied in this study were sourced from primary data. To determine the sample in this study, a cluster system was used which was carried out in Keranggan Village, Sekernan District, for cage farmers who had a total of 6 cages, with a sample of 25 respondents who were taken directly to all cage farmers. The data were analyzed using the analysis of the financial feasibility of tilapia cage cultivation with the formula for calculating NPV, IRR, Net Benefit Cost Ratio (B/C Ratio), and PP analysis. The results of the research analysis on the characteristics of respondents based on gender show that all respondents are male owners of tilapia cage cultivation business in Keranggan Village, respondents aged 54-63 years are 4 people or 16 percent of respondents are respondents of productive age. Based on the level of education, these results indicate that most of the respondents have met the 12-year compulsory education standard. Respondents have experience for 4-6 years, which is 28 percent. From Figure 1.3, it is known that the respondents are experienced enough in running a tilapia cultivation business in Keranggan Village, Sekernan District, Muaro Jambi Regency so that in practice the respondents can increase their business production. Characteristics of respondents based on the number of dependents who do not have or only themselves as many as 4 people or 16 percent who have dependents 1 child, then those who have dependents of 2 children are 7 people or 28 percent, the number of dependents of 3 children is 6 people or 24 percent, the number of dependents is 4 children as many as 4 people or 16 percent. The results of the feasibility of the cage business show that the results of the analysis of tilapia rearing in cages in Keranggan Village are currently financially feasible with an NPV value of Rp. 2,097,227 Net Benefit Cost Ratio (B/C Ratio) 1,235, IRR (Internal Rate of Return) 12.80%, Payback Periods (PP) obtained for 0.6695 years (6 months 24 days).